Mapping Intellectual of Student Well-Being, Literacy, and Numeracy in Primary Education in the 21st Century - Yeyen Febrilia; Azka ‘Afifah; Irpan Zuhri; Rahma Aini; Sindy Sataroh; Ulyma Tahara Arisandi (Contemporary Education and Community Engagement (CECE), 2026)
The increasing complexity of educational systems has intensified interest in understanding the relationships among student well-being, literacy, and numeracy in primary education. While literacy and numeracy are recognized as essential competencies for lifelong learning, growing evidence indicates that students’ psychological, emotional, and social well-being plays a critical role in shaping academic achievement and learning outcomes. Despite the expanding literature, a comprehensive overview of the intellectual structure and thematic evolution of this research area remains limited. Address this gap, this study conducted a bibliometric analysis of global research on student well-being, literacy, and numeracy in primary education using 144 Scopus-indexed publications published between 2011 and 2026. Data were analyzed using the Bibliometrix R Package and Biblioshiny, combining performance analysis and science mapping techniques, including publication trends, citation patterns, author productivity, source impact, institutional contributions, international collaboration, keyword co-occurrence, thematic evolution, co-citation networks, and bibliographic coupling. The results reveal a rapidly growing field with an annual growth rate of 21.25%. Australia emerged as the leading contributor, while Positive Psychology, Self-Determination Theory, Social-Emotional Learning, and school mental health formed the principal intellectual foundations. Thematic development demonstrates a transition from general well-being studies toward integrated investigations connecting psychological well-being with literacy achievement, numeracy development, educational resilience, and digital learning environments. Emerging research directions include digital well-being, learning analytics, and artificial intelligence in education. Based on these findings, the study proposes a Well-Being-Literacy-Numeracy Ecosystem Framework, positioning student well-being as a fundamental mechanism supporting literacy and numeracy development and promoting holistic educational success in primary education.